Narrativas de si: trajetórias formativas de professores formadores iniciantes no ensino superior - Soares, Sebastião Silva (2019)
This study is part of the Research line of Knowledge and Educational Practices of the Post-graduation Program in Education at the Federal University of Uberlândia (UFU). The goal of this work was to understand how is constituted the formative trajectories of beginning teacher educators in federal institutions of Higher Education in the Northern region of Brazil. The methodological approach was linked to the field of oral life story in dialogue with narrative research and (self) biographical study, anchored in the ideas of Connelly and Clandinin (1995), Larrosa (2002), Bom Meihy (2000), Guimarães (2006), Thompson (1992), Nóvoa and Finger (2010), Ferrarotti (2010), Bolívar (2016), among others. The collaborators were six teacher’s trainers, in the initial phase of the teaching career in the university, acting in teaching training courses of Pedagogy, History and Field Education, of two institutions of Higher Education. As study methodology, the narrative interview was used, addressing teachers’ life story, training and professional development. For the narrative analysis we used an Interpretative-Comprehensive reading. The experiences reported revealed that the initial phase in university teaching was taken by the professors as a time of validation of the learning apprehended during the formative life and professional trajectory. From the findings in the research, it was understood that the formation of the beginning teacher in the teaching training courses studied was directly related to life experiences, in an alternating movement between learning and re-signification of personal and collective experiences, as a permanent process of review and training.